Music Communication in Juicy Luicy’s Lyrics: Emotional Voices of Generation Z - Hera Nur Aini; Zainal Abidin; Celvin Dwi Putra Mudianto (Universitas Islam Balitar, 2025)
This study aims to analyze the emotional representation in the lyrics of Juicy Luicy’s popular songs among Generation Z. Employing Roland Barthes’ semiotic framework and Stuart Hall’s theory of representation, this research explores how emotional meanings are constructed through linguistic and symbolic signs in the lyrics and how Generation Z audiences interpret them based on their social context. The study focuses on four songs: “Lantas”, “Tanpa Tergesa”, “Lampu Kuning”, and “Sialan